Impact of immunization campaign triggered by meningococcal outbreak – Tuscany, 2014-2018. (30th September 2020) - Bisordi, C; Mariotti, T; Fornili, M; De Vita, E; Innocenti, F; Baglietto, L; Tavoschi, L; Lopalco, P
Abstract: In 2015-2016, an outbreak of invasive meningococcal disease due to Neisseria meningitidis C/cc11 occurred in Tuscany, Italy, and caused 62 cases. Regional Health Authority launched an immunization campaign using quadrivalent meningococcal conjugate vaccine (MEN) in April 2015. We assessed the impact of meningococcal outbreak on population vaccination coverage, considering a pre-outbreak (2014), outbreak (2015-2016) and a post-outbreak period (2017-2018) for MEN and other vaccinations (HPV and MMR). We included all individuals (>1 year) resident in Tuscany, who received at least one vaccination dose (MEN, HPV, MMR) in the study period. We sourced anonymous data from the regional centralised register on vaccine administered, date, place and dose (for multiple-dose vaccines); birth cohort; city of residence. We analysed vaccine administration by age, time, vaccine type. We modelled MEN vaccination rate as a function of number of cases in the previous month by a quasi-Poisson model (2015-2018), and HPV and MMR vaccination using an interrupted time series analysis (2014-2018). MEN vaccinations increased significantly in 2015-2016 (average doses/month were 3400 in 2014; 25492 in 2015; 47290 in 2016). MEN immunization coverage increased during the outbreak period, peaking for age class 20-45: from 3, 7% in 2014 to 10, 7% in 2015 and 20, 7% in 2016. MEN vaccination uptake showed a 50% increase (95% CI = 37 to 65%, P < 0.001) in the rate for each new case diagnosed in the previous month. HPV vaccination rate showed statistically significant decreasing trend in before the campaign (-3% per month, 95% CI = -1 to -5%, P = 0.004) disappearing afterwards (0%, 95% CI = -2 to 1%, P = 0.96); with no trend for MMR. The campaign successfully increased MEN coverage mostly among young adults, although vaccination demand was associated with occurrence of cases. The campaign did not affect routine vaccination programmes, and likely contributed positively to HPV uptake. Key messages: The immunization campaign triggered by meningococcal outbreak in Tuscany in 2015-2016 successfully increased coverage, mostly among young adults, without affecting routine vaccination programmes. During response campaign triggered by meningitis outbreak in Tuscany in 2015-2016, meningococcal vaccine uptake was influenced by the occurrence of cases.